A Molecular Modelling Approach for Designing a Novel Semisynthetic Metalloenzyme Based on Thermolysin - Jaafar, Ahmad Haniff (2006)
Current computational chemistry tools were used to solve the problem of screening for the best conformation of potential protein-ligand-metal complex in designing a novel semisynthetic metalloenzyme. The computational tools used were Computational Atlas Topography of Protein (CASTp), a sophisticated molecular modeling environment InsightII, a conventional drug-docking algorithm Autodock 3.05 and a schematic diagram for protein-ligand interactions for a given PDB file LIGPLOT. Overall 48 protein pockets on the thermolysin structure were measured using CASTp and the four biggest pockets based on their number of residues and surface area were identified to be suitables site for the modification. Ten different sizes and multifunctional groups of chemical ligands were studied for their thermodynamic valuation using the AutoDock 3.05 program. For further modification, phosphoethanolamaine (PSE), phenylalanine (PHE), phenylacetic acid (PAC) and phenanthroline (PHN) were chosen as they possessed the lowest docking energy of -8.49, -8.34, -7.33 and -7.06 kcal/mol, respectively. Non-covalent interactions included hydrogen bonding and hydrophobic interaction between the ligands and the thermolysin were determined using CASTp. The result showed that larger ligands with multifunctional groups such as PSE and PHE showed higher number interactions compared to the smaller ligands. In terms of specific pockets for the modification, different protein-ligand complexes showed different suitable pockets; complex of thermolysin and PSE ligand at pocket 45, complex of thermolysin and PAC ligand at pocket 48 and both complexes of thermolysin with PHE and PHN ligands at pocket 45, respectively. To verify the final metal ion orientation, three procedures were conducted to narrow down the number of possible conformations for the modification. From four tested metal ions (Ca2+, Mg2+, Fe2+ and Zn2+ ), Ca2+ was identified to be the most favorable metal ion for the modification. It had orientated within an allowed geometry in all tested protein ligand complexes. Meanwhile, both Mg2+ and Fe2+ were identified as favorable metal ions in KEI-PSE and KEI-PAC complexes, respectively. Zn2+ however, showed non favorable docking in all tested complexes due to improper parameterized file for zinc ion in AutoDock.